Evliya Çelebi's journey from Bursa to the Dardanelles and Edirne : from the fifth book of the Seyahatname. - Karateke, Hakan T. (Evliyā Çelebi's Book of Travels, 2013)
Evliyā Çelebī's Journey from Bursa to the Dardanelles and Edirne is comprised of an edition and translation of the relevant section from Evliyā's Book of Travels detailing the 29-day journey he undertook in the autumn of 1659 from Bursa to Edirne via the Dardanelles strait. Evliyā travelled in the retinue of grand vizier Köprülü Mehmed Pasha and Sultan Mehmed IV, who was travelling to inspect the two castles that were being built at the southern tip of each side of the Dardanelles. This was the only trip that Evliyā made to the region between Bursa and Edirne. This edition also includes a detailed annotated index of people and places as well as the geographic coordinates of all the locations and buildings mentioned in the text.